Peran Rubi Community dalam Penerapan Strategi Public Relations Untuk Membangun Citra Merek Avoskin Beauty - Ilma Nafi’atul Jannah; Hadiati; Novita Damayanti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study examines the role of the RUBI Community in implementing public relations strategies to build the brand image of Avoskin Beauty. Using a qualitative case study approach within a constructivist paradigm, the research applies New Media theory, the R.A.C.E process, and the 7C’s model. Data were collected through triangulation of in-depth interviews, participant observation, and documentation, and analyzed using the Miles & Huberman model. The findings reveal that the RUBI Community functions both as a communication channel and as a CSR initiative focusing on women’s empowerment. This dual role significantly enhances Avoskin’s image as an innovative and affordable brand, while strengthening consumer loyalty. The study concludes that community-based PR strategies can effectively foster emotional engagement and brand advocacy, offering practical implications for beauty brands seeking to integrate social values into their communication strategies.